Nitrogen Gas Quenching Pressure Effect on Bs S155 Alloy Steel in Vacuum Furnace - Hasanudin, Agus Mulyadi; Siradj, Eddy Sumarno (UI Scholars Hub, 2023)
The production of metal and alloy products requires the use of heat treatment, when during the heat treatment process, quenching is a crucial step. The quenching medium can be anything from water, a salt bath, oil, air and gas. In a vacuum furnace, pressurized gas, most frequently nitrogen (N2) gas, serves as one of the quenching mediums. One of the drawbacks of the quenching process is the distortion and dimensional change of the parts. This paper aims to investigate the influence of nitrogen gas quenching pressure on the distortion and dimensional change of aerospace actuator gear planet parts made from BS S155 alloy steel. BS S155 is the British aerospace equivalent of U.S. steel grade 300M (4340M), it is a vacuum melted grade supplied in the normalized and softened condition to allow for final heat treatment and widely used such as undercarriage components, gears, and shafts. Gear planet parts heat treated and quenched with pressurized nitrogen gas as an independent variable of the experiment, then double temper as required on the specification. Following this, optical microscopes, tensile and hardness tests in accordance with ASTM E8 and ASTM E92, as well as dimensional analysis, were used to characterize the parts. The results demonstrate that nitrogen gas quenching at 1.5 bar pressure improves dimensional stability without degrading the mechanical properties of the part, with the maximum dimensional distortion being 0.06% or 20 µm, while the mechanical properties result for the two nitrogen gas quenching pressures were less significantly different.